Сytokines as promising diagnostic and prognostic biomarkers of microvascular complications of diabetes - V. V. Klimontov; К. R. Mavlianov (Сибирский научный медицинский журнал)
Classical knowledge about the pathogenesis of diabetes and its complications in recent years has been supplemented by ideas about the role of chronic inflammation. It has been established that inflammatory reactions play a role in the beta cell dysfunction, the formation of insulin resistance and remodeling of the vascular wall. Cytokines, soluble low molecular weight proteins and peptides that perform informational and regulatory functions, play central role in the development of inflammation. A wide range of biological activity and involvement in many aspects of pathogenesis make it possible to consider cytokines as promising molecules for diagnosing and predicting the complications. In this review, we summarize data from studies that assessed the role of cytokines as diagnostic and prognostic markers for the development of microvascular diabetic complications. Current data indicate that angiogenic and pro-inflammatory cytokines (VEGF, TNF-α, IL-6, IL-8, IL-15, IL-17, MCP-1, IP-10, INF-γ, PEDF, etc.) are promising biomarkers for proliferative diabetic retinopathy, especially when their local production is assessed (in vitreous, aqueous humor and tears). The role of these molecules as biomarkers of non-proliferative diabetic retinopathy and diabetic macular edema needs further research. Serum proinflammatory and fibrogenic cytokines (primarily MCP-1, IL-6, TNF-α, YKL-40, TGF-β and bFGF) and cytokine receptors (sTNFR1, sTNFR2) are considered as promising diagnostic and prognostic markers of diabetic kidney disease. Urinary excretion of IL-6 and MCP-1 turned out to be a predictor of the progression of diabetic nephropathy. Multi-bead assay and mass spectrometry make it possible to study cytokine panels in small samples of biological material. Combined biomarkers, including several cytokines, may increase the reliability of the prognosis of diabetic complications.